Research on Financial Performance Evaluation of Company W Based on Factor Analysis Method - Li, Haobin (Asia Pacific Economic and Management Review, 2025)
As a core industry supporting global technological transformation, the semiconductor industry not only profoundly reshapes the technical pathways of traditional fields such as energy management, transportation, and medical diagnosis but also serves as a strategic cornerstone for ensuring the stable operation of the modern electronic information industry and driving innovation breakthroughs in artificial intelligence and the Internet of Things. Against the policy background of China vigorously promoting the autonomy of the semiconductor industry and encouraging breakthroughs in core technologies, domestic semiconductor enterprises are facing a critical period of opportunity for large-scale development. However, inherent characteristics of the industry, such as high R&D cost pressures, barriers posed by core technology patents, short product life cycles, and intensifying global market competition, also expose enterprises to operational risks like insufficient profit stability and pressure on capital chains. This paper takes Company W, a leader in the field of semiconductor image sensors, as the research object. Eight financial indicators are selected from four dimensions: profitability, solvency, operation, and growth. Factor analysis is conducted using SPSS to calculate performance scores and analyze its financial performance. Based on the analysis, optimization suggestions such as cost control and capital allocation are proposed, providing references for the sustainable development of Company W and other enterprises in the same industry.